Una lectura girardiana de los sistemas totalitarios modernos: el caso de Cuba. - Rodríguez González, Raisiel Damián (2020)
Girard (1986) claims that "in modern totalitarianism a whole set of primitive characteristics reappears". Our work is framed under this line of thought. We will try to make a reading of the totalitarianism that was founded in the island of Cuba in 1959 and see how it has developed. Can the essential elements of the archaic sacrificial systems be found within the Cuban totalitarian system? This is the question to which we will try to give an answer.